Penerapan Growth Mindset Theory, Strategic Theory dan Global Studies and Carrier pada Siswa Sekolah Menengah Atas Negeri 3 Kota Tangerang Selatan - Sumantri, Indra Iman; Priyadi, Eko Sasongko; Suryani, Eny (ABDIMAS Iqtishadia, 2023)
These various social problems are economic inequality, poverty, high unemployment, uncontrolled population growth, rising crime rates and the increasingly eroding of rural areas by development. As a result, it is difficult for some people to get access to the basic needs they are entitled to, such as obtaining education. This condition occurs because some people have financial limitations to obtain education. This fact can be seen in rural areas or sub-urban areas, an area that is located between urban and rural areas. One of the problems faced by high schools in general and students in particular is the lack of information for students who wish to obtain scholarships to continue their education to a higher level of education. To meet the need for information about higher education pathways in the country and abroad, especially overseas, several teaching staff of the Accounting Study Program, Faculty of Economics and Business, Pamulang University carry out a Community Service Program with the theme "Implementation of Growth mindset theory, strategic theory dan global study and carrier abroud for State Senior High School 3 Students in South Tangerang City ".